Analysis of air quality and nighttime light for Indian urban regions. (June 2016) - Misra, Prakhar; Takeuchi, Wataru
Abstract: Indian urban regions suffer severe air pollution issues. A 2014 study by WHO highlighted that out of 20 cities globally with worst air quality, 13 lie in India. Although insufficient ground monitoring data and incomplete air pollution source characterization impedes putting policy measures to tackle this issue, remote sensing and GIS can overcome this hurdle to some extent. To find out how much of this hazard is due to economic growth, past researches have tried to make use of socio-economic growth indicators like GDP, population or urban area to establish its correlation with air quality in urban centres. Since nightlight has been found to correlate well with economic conditions at national and city level, an attempt has been made to analyse it with air quality levels to find regions with high contribution of anthropogenic emissions. Nighttime light activity was observed through DayNight Band (DNB) of VIIRS sensor while the air quality levels were obtained for ANG and AOD (using MODIS sensor) and SO2 and NO2 (using OMI sensor). We have classified Indian landmass into 4 air-quality and DNB classes: LowLight- HighPollution, HighLight-HighPollution, LowLight-LowPollution and HighLight- LowPollution for each air quality species using June 2014 data. It was found that around half of urban regions show high AOD and ANG values. On the other hand almost all urban regions exhibit high SO2 and NO2 values.